Septuaginta: A Reader's Edition: Vol. I: Genesis - 4 Maccabees - Gregory R. Lanier; William A. Ross (USA Hendrickson Publishers, 2019)
"Septuaginta: A Reader's Edition offers the complete text of the Greek Old Testament as it appears in the Rahlfs-Hanhart revised Septuaginta, laid out in a clear and readable format. All deuterocanonical books are included, as well as all double-texts, which are presented on facing pages for easy textual comparison. In order to facilitate natural and seamless reading of the text, every word occurring 100 times or fewer in the Rahlfs-Hanhart text (excluding proper names)--as well as every word that occurs more than 100 times in the Rahlfs-Hanhart text but fewer than 30 times in the Greek New Testament--is accompanied by a footnote that provides a contextual gloss for the word and (for verbs only) full parsing. Additionally, an appendix provides a complete alphabetized list of common vocabulary (namely, all the words that are not accompanied by a footnote), with glosses and (as applicable) comparison of a word's usage in the Septuagint to its usage in the New Testament"--
Volume I: Genesis - 4 Maccabees -- Volume II: Psalms - Bel and the Dragon.
Keywords: Holy Bible Texts and Translations (3fUhU hJQLeGJ GdcJGH GdebOSs; Bible